McGraw-Hill concise encyclopedia of physics. (New York : McGraw-Hill, 2005)
Hundreds of well-illustrated articles explore the most important fields of science. Based on content from the McGraw-Hill Concise Encyclopedia of Science & Technology, Ninth Edition, the most widely used and respected science reference of its kind in print, this quick-reference guide delivers: detailed, well-illustrated explanations, not just definitions; hundreds of concise yet authoritative articles in each volume; an easy-to-understand presentation, accessible and intersting to non-specialists; a portable, convenient format; and bibliographies, appendices, and other information to supplement the articles.
Articles, A-Z -- Appendix. Bibliographies ; Base units of the International System ; Prefixes for units in the International System ; Derived units of the International System ; Some common units defined in terms of SI units ; Conversion factors for the U.S. Customary System, metric system, and International System ; Fundamental constants ; The fundamental particles ; Internal energy and generalized work ; The 14 Bravais lattices ; Dimensional formulas of common quantities ; Physical properties of optical materials ; Types of radioactivity ; Principal spectral regions and fields of spectroscopy ; Defining fixed points of the International Temperature Scale ; Primary thermometry methods ; Biographical listing.
Includes bibliographical references and index.
Keywords: Physics -- Encyclopedias; Physique; Physique -- Dictionnaires anglais